2010
DOI: 10.3390/ph3040961
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Penetrating Peptides—Mechanisms of Cellular Uptake and Generation of Delivery Systems

Abstract: The successful clinical application of nucleic acid-based therapeutic strategies has been limited by the poor delivery efficiency achieved by existing vectors. The development of alternative delivery systems for improved biological activity is, therefore, mandatory. Since the seminal observations two decades ago that the Tat protein, and derived peptides, can translocate across biological membranes, cell-penetrating peptides (CPPs) have been considered one of the most promising tools to improve non-invasive ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
229
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(246 citation statements)
references
References 182 publications
(377 reference statements)
11
229
0
1
Order By: Relevance
“…However, regardless of the model, the translocation of large molecules requires a large destabilization of cell membrane, which is not correlated with the observed low cytotoxicity of CPPs and their conjugates. Thus, none of the presented models can fully explain the results of experiments with different CPPs, suggesting a contribution of alternative mechanisms of peptides' internalization, especially during penetration combined with molecular delivery [19].…”
Section: Direct Translocationmentioning
confidence: 88%
See 3 more Smart Citations
“…However, regardless of the model, the translocation of large molecules requires a large destabilization of cell membrane, which is not correlated with the observed low cytotoxicity of CPPs and their conjugates. Thus, none of the presented models can fully explain the results of experiments with different CPPs, suggesting a contribution of alternative mechanisms of peptides' internalization, especially during penetration combined with molecular delivery [19].…”
Section: Direct Translocationmentioning
confidence: 88%
“…The results of internalization of CPPs into cells even at low temperatures excluded endocytosis as the main mechanism of transport of peptides into the cell and suggested the existence of an alternative mechanism which required no energy [19]. Such transport mechanism was naturally observed for CPPs isolated from venoms: mastoparan [20] from V. lewisii wasp or crotamine [21] from rattlesnake, which interact directly with cell membrane (Table 1).…”
Section: Direct Translocationmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been reported that the excess CPP could not affect the amount of uptake cargo. Trabulo et al (2010) demonstrated that there was no enhanced cellular internalization of siRNA after extensive purification of CPP/siRNA conjugates from the excess cationic peptide in the conjugation reaction. The result from cytotoxicity study showed that V peptide was safer than Tat peptide, indicated by higher cell viability.…”
Section: Discussionmentioning
confidence: 99%